Nutrition controversies - Halula, Wes.; Learning Zonexpress (Australia : VEA, 2009)
'Join ... two teens as they take a closer look at controversial nutrition topics to get the straight facts on food safety, organic foods, genetically engineered foods, food allergies, MSG, functional foods, dietary supplements and more'--Container.
Camera, Jim Kunz, Kevin Sambells, Wes Halula ; editors, Wes Halula, Jenica Halula, Jason Naumann.
Hosts: Genevieve Helm and Ricky Castleberry.
DVD format.
Keywords: Nutrition; Food analysis; Food Safety